Corporate restructuring : (the World Bank, 2005)
This timely volume takes an in-depth look at the efforts to fight corporate crisis in Indonesia, Korea, Malaysia, and Thailand, among others, and discusses the vital role of governments in securing and enabling legal system, effective out-of-court workouts, supportive tax regimes, and complementary policy and regulatory initiatives to confront systemic corporate distress